Community Empowerment Model Based on Independence in Administration Alert Village Health Sector - Suparji, Suparji; Nugroho, Heru Santoso Wahito; Sunarto, Sunarto (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Introduction: The success of âAlert villagesâ (âalert villageâ) can be explained using an independence-based